2016
DOI: 10.1159/000444928
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of the Phosphatidylinositol 3-Kinase Pathway in Non-Small Cell Lung Cancer Cells Isolated from Pleural Effusions

Abstract: Objectives: We hypothesised that it was possible to quantify phosphorylation of important nodes in the phosphatidylinositol 3-kinase (PI3K) pathway in cancer cells isolated from pleural effusions of patients with non-small cell lung cancer (NSCLC) and study their correlation to somatic mutations and clinical outcomes. Materials and Methods: Cells were immunomagnetically separated from samples of pleural effusion in patients with NSCLC. p-AKT, p-S6K and p-GSK3β levels were quantified by ELISA; targeted next-gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…Immunohistochemistry is the most common method of measuring PD-L1 in the clinical context with well documented issues with standardization across platforms [ 24 ] and we propose that the jurkat co-culture system be investigated in the clinical context. This could involve the isolation of cancer cells from circulating tumour cell platform or serous effusions [ 25 ] [ 26 ] and is worthy of further investigation. We recognize the experiments in immunocompetent animal models will offer the most robust validation of the functional relevance of PDL-1 expression as a mechanism of resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Immunohistochemistry is the most common method of measuring PD-L1 in the clinical context with well documented issues with standardization across platforms [ 24 ] and we propose that the jurkat co-culture system be investigated in the clinical context. This could involve the isolation of cancer cells from circulating tumour cell platform or serous effusions [ 25 ] [ 26 ] and is worthy of further investigation. We recognize the experiments in immunocompetent animal models will offer the most robust validation of the functional relevance of PDL-1 expression as a mechanism of resistance.…”
Section: Discussionmentioning
confidence: 99%
“…We believe that such a reconstructive approach from single molecular alterations to whole tumor biology has great potential because it has been previously shown that freshly dissociated cells from the tumor mirror the genotypic characteristics of the tumor [24,25]. This method is also versatile because various sources of samples such as biopsies, blood, peritoneal (ascites), urine, pleural or cerebrospinal fluids can be exploited to harvest cancer cells [25,[47][48][49][50]. Moreover, in prostate cancer, the anatomical position of the prostate makes prostate biopsies and urine important sources of cancer cells, which could facilitate the translation of the technology into the clinics.…”
Section: Discussionmentioning
confidence: 99%
“…p‐S6K levels were significantly higher in tumors carrying at least one mutation compared with those that did not carry any. Higher levels of p‐AKT and p‐S6K were associated with shorter survival in univariate analysis, and the latter was retained in multivariate analysis 36 …”
Section: Cellular Fractionmentioning
confidence: 99%